2001
DOI: 10.1002/qua.1611
|View full text |Cite
|
Sign up to set email alerts
|

Molecular view of charge exchange in ion–C60 collisions

Abstract: ABSTRACT:We present a theoretical study of charge transfer in H + + C 60 and He 2+ + C 60 collisions using an extension of the molecular time-dependent method of ion-atom collisions. Energy-correlation diagrams have been evaluated for the corresponding (C 60 -H) + and (C 60 -He) 2+ quasi-molecules. Single and double charge-transfer cross sections in C 60 + He 2+ collisions are reported for the first time. The results show that double charge-transfer cross sections are only one order of magnitude smaller than s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The latter has been estimated from numerical simulations of the electron dynamics in sodium clusters [80], yielding a ≃ 0.4 fs −1 eV −2 , which is also compatible with the analytical prediction given by the random phase approximation [82]. The electron temperature is computed instantaneously during the simulation, and plugged into the expression for the collision rate (47). It is important to underline that the above model for e-e collisions, though simple, is completely self-contained and requires no additional ad-hoc parameters.…”
Section: Electron-electron Collisionssupporting
confidence: 67%
See 1 more Smart Citation
“…The latter has been estimated from numerical simulations of the electron dynamics in sodium clusters [80], yielding a ≃ 0.4 fs −1 eV −2 , which is also compatible with the analytical prediction given by the random phase approximation [82]. The electron temperature is computed instantaneously during the simulation, and plugged into the expression for the collision rate (47). It is important to underline that the above model for e-e collisions, though simple, is completely self-contained and requires no additional ad-hoc parameters.…”
Section: Electron-electron Collisionssupporting
confidence: 67%
“…This approach is restricted to small metal clusters. The interaction of strong femtosecond laser pulses with a C 60 molecule (which possesses 240 delocalized electrons and can therefore be considered as a metallic nano-object [47]) has been investigated in Ref. [48] by employing a TDDFT approach.…”
Section: Applicationmentioning
confidence: 99%
“…By using the actual value of the C 60 radius, which is 6.7 a 0 (refs 40, 41) equivalent to the distances between the geometrical centre of the cage and the carbon atoms, the estimated value of Δ α is 18 a.u.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies [20][21][22][23][24][25] have demonstrated that this model is able to mimic most of the relevant features obtained by using much more sophisticated first principle calculations [1,26]. Simplified jellium-based models have the advantage to allow the computation of the linear response with the associated many-body effects (e.g.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Following Perdew and Zunger [28], we have added a self-interaction correction that restores the correct asymptotic behaviour of the effective potential. In the past, this procedure has been successfully applied to the study of both ground-and excitedstate properties of atoms [29], molecules, small metal clusters [30,31] and C 60 [19,[21][22][23][24][25]. Both jellium approximation and self-interaction correction have been used with success in the interpretation of resolved spectra of Rydberg series in C 60 [21].…”
Section: Theoretical Methodsmentioning
confidence: 99%